Traffic flow characteristics along Federal Highway (Kuala Lumpur — Klang) / Abdul Rahman Jaffar and Ramli Noordin - Jaffar, Abdul Rahman; Noordin, Ramli (1985)
In our project, we were to study the pattern and traffic flow characteristics of the Federal Highway, Kuala Lumpur - Klang. At present, its volume seems to have been exceeded the design limit tremendously and recorded data shows that it has the greatest traffic volumes per day compared to other highways in Malaysia which results in frequent traffic jam along with. The main objective of the project is to collect travel flow data of traffic volume and their characteristic-pattern by locating some station-survey along the route to forecast travel demands, analyse road capacity and to suggest plans for future development. Traffic flow at a given location depends on numerous factors peculiar to that site. As would be expected, it varies by hours of the day, days of the week, and months of the year. Likewise, its character changes; for example the percentage and kind of Lorries is a function both time of the day and the contributing area. The number of vehicles passing a given point during a specified period of time, or the number of vehicles that pass over a given section of a lane or a roadway during a specified period of time is the volume measured. The total volume during a given time period, in whole days greater than one day and less than one year, divided by the number of days in that time period, commonly abbreviated as ADT. For the 'average annual daily traffic' commonly called as AADT, as volume may be stated on an hourly basis, such as the 'hour observed traffic volume' or 'estimated thirtieth-hour volume', which is commonly used.